Selection and characterization of the inheritance of resistance of Spodoptera frugiperda (Lepidoptera: Noctuidae) to chlorantraniliprole and cross‐resistance to other diamide insecticides. Issue 10 (25th March 2019) - Bolzan, Anderson; Padovez, Fernando EO; Nascimento, Antonio RB; Kaiser, Ingrid S; Lira, Ewerton C; Amaral, Fernando SA; Kanno, Rubens H; Malaquias, José B; Omoto, Celso
Abstract: BACKGROUND: Understanding the genetic basis of insect resistance to insecticides can help to implement insecticide resistance management (IRM) strategies. In this study, we selected a strain of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) resistant to chlorantraniliprole using the F2 screen method, characterized the inheritance of resistance and evaluated patterns of cross‐resistance to other diamide insecticides. RESULTS: The chlorantraniliprole‐resistant strain (Chlorant‐R) was selected from a field‐collected population with an estimated allele frequency of 0.1316. The estimated median lethal concentration (LC50 ) values were 0.011 and 2.610 µg a.i. cm –2 for the susceptible (Sus) and Chlorant‐R strains, respectively, resulting in a resistance ratio (RR) of 237‐fold. The LC50 values of the reciprocal crosses were 0.155 and 0.164 µg a.i. cm –2, indicating that resistance is autosomally inherited. Resistance was characterized as incompletely recessive and monogenic at concentrations close to the recommended field rates of chlorantraniliprole. Survival of the resistant strain and heterozygous larvae in maize plants treated at the field rate was ∼ 60 (similar to the susceptible strain on untreated maize) and 15%, respectively. The Chlorant‐R strain showed low cross‐resistance to cyantraniliprole (RR ∼ 27‐fold) and very high cross‐resistance to flubendiamide (RR > 42 000‐fold). CONCLUSIONS: The frequency of chlorantraniliprole resistance allele was moderately high in a field‐collected population of S. frugiperda . The inheritance of chlorantraniliprole resistance was characterized as autosomal, incompletely recessive and monogenic. S. frugiperda showed cross‐resistance to other diamide insecticides. These results provide essential information for the implementation of IRM programs to preserve the useful life of diamide insecticides for controlling S. frugiperda in Brazil. © 2019 Society of Chemical Industry Abstract : We selected and characterized the inheritance of chlorantraniliprole resistance by Spodoptera frugiperda (Lepidoptera: Noctuidae) and evaluated patterns of cross‐resistance to other diamide insecticides.